2018
DOI: 10.21037/gs.2018.08.05
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative imaging for breast conservation surgery—do we need more than conventional imaging for local disease assessment?

Abstract: Breast conservation surgery (BCS) is offered for early breast cancer. Conventional imaging with mammography and ultrasound would have been performed prior to surgery. This article considers other imaging modalities available [such as 3D tomosynthesis, magnetic resonance imaging (MRI), contrastenhanced spectral mammography, positron emission mammography (PEM), breast-specific gamma imaging (BSGI) and cone beam computed tomography (CBCT)] and discusses the evidence for these in terms of diagnostic accuracy and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…However, MRI requires a considerable capital investment, and lengthy examination times can produce patient discomfort and claustrophobia. There is also an ongoing concern that preoperative MRI shows clinically irrelevant tumors and increases mastectomies without patient benefit 17,18 . In recent years, clinical use of contrast-enhanced spectral mammography has shown promise for neoadjuvant therapy monitoring 19 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, MRI requires a considerable capital investment, and lengthy examination times can produce patient discomfort and claustrophobia. There is also an ongoing concern that preoperative MRI shows clinically irrelevant tumors and increases mastectomies without patient benefit 17,18 . In recent years, clinical use of contrast-enhanced spectral mammography has shown promise for neoadjuvant therapy monitoring 19 .…”
mentioning
confidence: 99%
“…There is also an ongoing concern that preoperative MRI shows clinically irrelevant tumors and increases mastectomies without patient benefit. 17,18 In recent years, clinical use of contrast-enhanced spectral mammography has shown promise for neoadjuvant therapy monitoring. 19 Notwithstanding, studies in large patient populations are still needed to validate initial findings.…”
mentioning
confidence: 99%
“…Hence, a reductionist, or minimalist approach to fulfil oncologic requirements may provide optimal results (32,33). Such an approach would require an integration of appropriate preoperative imaging, careful surgical planning and detailed pathologic examination (34,35). This is consistent with the argument by Marescaux et al that iatrogenic impact should be reduced in surgical innovation for patient safety and quality of life (36).…”
Section: The Art Of Bctmentioning
confidence: 64%
“…It has been reported that the ratio of multifocal/multicentric BC ranges from 4 to 50% in different series [33][34][35][36][37]. Addition of MRI to the work up increases multifocal/multicentric tumor rate [38]. Meta-analysis of data from nineteen studies showed that MRI detected additional disease in 16% of women leading to conversion from wide local excision to mastectomy in 11.3% of cases [33,39].…”
Section: Discussionmentioning
confidence: 99%